INDIVIDUAL AND INTERACTIVE UTILITY OF BIOLOGICAL AND PHYSICAL INVIGORATION FOR VARIOUS CARROTS SEEDS ORDERS AND STUDY THEIR FIELD PERFORMANCE - Aseel M.H. H. Al-Khafaji; Kadhim D. H. Al-jubouri (Iraqi journal of agricultural science, 2024)
The purpose of this research is assessing the significance of biological and physical seeds invigoration of different aged carrot seeds orders and study their field performance. An implementation of field experiment at station (A) College of Agricultural Engineering Sciences - University of Baghdad during fall season 2021-2022. The experimental design arranged using split plot within RCBD. As carrot seeds order considered main plots (primary P, secondary S, tertiary T) and seeds invigoration treatments sub plots (untreated seeds C0, biological B, Physical G, B+G) with three replicates (3X4X3). The interaction treatment PBG (biological+physical treated primary seeds order) reveals significance in majority of research traits such as  field emergence percent, carrot total carotenoids, scavenging percent, total yield (97.67%,12.66mg.100g, 88%, 126.1 ton.ha-1) respectively in compare to untreated tertiary seeds order  (TC0).